USB 2.0 Digital Camera Characterization for Optimizing the Making of High Power RGB-LED Fluorescence Imaging System - Apriani, Atika; Rifai, Rochan; Rakhmadi, Frida Agung; Khamidinal (Proceeding International Conference on Science and Engineering, 2020)
This research aims to obtain the focal length and radial and tangential distortion of a USB 2.0 digital camera. This research was conducted in three stages namely preparation of tools and materials, camera characterization, and data processing. The tools used in this study include a USB 2.0 digital camera and MATLAB R2013a software, while the object is a collimator board. Characterization of digital cameras is done through data collection with a distance variation of 3 cm until 15 cm, then the data obtained is processed using MATLAB R2013a software to obtain the focal length and radial distortion and tangential distortion values. The USB camera that used has the characteristic focal length and radial distortion and certain tangential distortion for each distance.